A Multi-Institutional Experience of Proton Beam Therapy for Sinonasal Tumors - Nathan Y. Yu, MD (Advances in Radiation Oncology, 2019)
Purpose: To report the outcomes of sinonasal tumors treated with proton beam therapy (PBT) on the Proton Collaborative Group registry study. Methods and Materials: Sixty-nine patients with sinonasal tumors underwent curative intent PBT between 2010 and 2016. Patients who received de novo irradiation (42 patients) were analyzed separately from those who received reirradiation (27 patients) (re-RT). Median age was 53.1 years (range, 15.7-82.1; de novo) and 57.4 years (range, 31.3-88.0; re-RT). The most common histology was squamous cell carcinoma in both groups. Median PBT dose was 58.5 Gy (RBE) (range, 12-78.3; de novo) and 60.0 Gy (RBE) (range 18.2-72.3; re-RT), and median dose per fraction was 2.0 Gy (RBE) for both cohorts. Survival estimates for patients who received de novo irradiation and those who received re-RT were calculated using the Kaplan-Meier method. Results: Median follow-up for surviving patients was 26.4 months (range, 3.5-220.5). The 3-year overall survival (OS), freedom from distant metastasis, freedom from disease progression, and freedom from locoregional recurrence (FFLR) for de novo irradiation were 100%, 84.0%, 77.3%, and 92.9%, respectively. With re-RT, the 3-year OS, freedom from distant metastasis, FFDP, and FFLR were 76.2%, 47.4%, 32.1%, and 33.8%, respectively. In addition, 12 patients (17.4%) experienced recurrent disease. Re-RT was associated with inferior FFLR (P = .04). On univariate analysis, squamous cell carcinoma was associated with inferior OS (P < .01) for patients receiving re-RT. There were 11 patients with acute grade 3 toxicities. Late toxicities occurred in 15% of patients, with no grade ≥3 toxicities. No patients developed vision loss or symptomatic brain necrosis. Conclusions: As one of the largest studies of sinonasal tumors treated with PBT, our findings suggest that PBT may be a safe and efficacious treatment option for patients with sinonasal tumors.